Sifat Fungsional Pati Ubi Kelapa Kuning (Dioscorea alata) dan Pemanfaatannya sebagai Pengental pada Saus Tomat - U Ulyarti; L Lavlinesia; N Nuzula; N Nazarudin (agriTECH, 2018)
The aim of this research was to determine the functional properties of yellow greater yam’s starch (Dioscorea alata) and its ability to acts as thickening agent for tomato sauce. This research was carried out in 2 stages: starch extraction followed by determination of its physical and functional properties and production of tomato sauce using completely randomized design with 5 levels of starch concentration and 4 replications. The levels were 0, 1, 2, 3 and 4% which was calculated from tomato pulps. Functional properties of yellow greater yam’s starch showed the capability as thickening agent but had quite high setback value.  The result showed that the concentration of yellow greater yam’s starch significantly affect viscosity and syneresis (p <0 .01) and a* value (p < 0.05) but did not affect water content, total soluble solid, L* and b* of the tomato sauce.  Although creates an obvious color difference (ΔE>3), the concentration of 2% yellow greater yam’s starch is proposed to be used as thickening agent in tomato sauce producing tomato sauce without syneresis during a week of storage, viscosity 4.85 Poise, total soluble solid 44.8 obrix, L* 50.75, a* 50.75, b* 51.30 and overal acceptance “rather like” to “like”.